Public transport accessibility and housing value uplift: Evidence from the Docklands light railway in London. Issue 3 (September 2019) - Song, Zhe; Cao, Mengqiu; Han, Tingting; Hickman, Robin
Highlights: The impacts of the DLR south-eastern branch produced a higher premium on house prices. Property tenure is most influential in determining housing values. Houses that are detached, newly built, freehold and on brownfield sites are likely to be more expensive. Each station catchment area may generate approximately £5-8 million residential valueuplift. Abstract: Public transport infrastructure is essential to city development, improving accessibility and allowing people to engage in activities, allowing travel by environmentally-friendly modes, and also creating economic benefits. This study investigates the impacts of public transport accessibility on development, examining changes in housing prices, and applying hedonic modelling. London's Docklands Light Railway (DLR) is selected as a case study. The findings show that residential properties in station catchment areas of the south-eastern and northern branches of the DLR have a premium respectively of 0.352% and 0.093% per 100 m proximity to a station. By assessing inclusive variables, it is found that housing value is also determined by the property's own features and the neighbourhood, particularly the property tenure. The detected housing value uplift implies that the provision of good public transport is crucial in policy making, especially in areas with poor public transport accessibility. Moreover, since transport investment is partly capitalised in housing projects, we suggest that future transport infrastructure investment and housing development should be set within a framework of value capture policies.